Building the Landing Zone for Site Reliability Engineering: A Multivocal Literature Review - Costa, Luiz Alexandre; Fontão, Awdren; Constantinou, Eleni; Santos, Rodrigo Pereira dos; Serebrenik, Alexander (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
In the era of software-intensive business (SiB), the interdependence between business and software is increasingly prominent. Organizations at the forefront of the digital revolution rely on complex systems to deliver innovative services and products. One of the major challenges is maintaining 24/7 online applications with consistent performance, a task that falls to both the development (Dev) and operations (Ops) teams. Traditionally, Dev focuses on innovation and new features, while Ops ensures the stability of the applications. This division leads to reliability gaps, especially in systems where availability is critical, such as financial services, e-commerce, or mission-critical applications. In such contexts, Site Reliability Engineering (SRE) offers a structured approach that applies Software Engineering (SE) practices to Ops, promotes reliability management through service-level objectives and error budgets, and reduces toil through automation. Given that several emerging practices in SRE occur outside scientific literature, we choose a multivocal approach to capture both theoretical advances and practical experiences. Our work aims to investigate what the multivocal literature is saying about the SRE approach, building the landing zone (a comprehensive foundation) for further studies. Thus, a multivocal literature review (MLR) was performed to identify practices, tools, benefits, and future perspectives from the point of view of researchers and practitioners.We selected 28 studies after applying the review procedures. Based on the results, we categorized SRE practices using the Stacey matrix to guide organizations in prioritizing their adoption. In addition, we propose a Flywheel model to illustrate the iterative and continuous nature of the SRE implementation.